Marine invasive macroalgae: Turning a real threat into a major opportunity - the biotechnological potential of Sargassum muticum and Asparagopsis armata - Pinteus, Susete (2018)
Marine invasive species are widely recognized as one of the worst threats to marine ecosystems integrity, un-balancing native communities, which may lead to paramount ecological and economic impacts. Within invasiveseaweeds, Sargassum muticum and Asparagopsis armata are recognized as successful invaders in Europe andAmerica. Despite several attempts to control the spread of marine invaders, until now, all have proven to beelusive, and therefore, alternative strategies should be embraced.Worldwide, seaweeds have been increasingly explored due to their ability to produce bioactive compounds.However, one of the main problems associated with the production/extraction of these bioactive compounds fornew products development, is the source availability and the potential negative environmental consequences ofthis exploitation.Within this framework, the use of invasive species to obtain natural bioactive compounds presents us with atwo-folded opportunity - high availability of the biological material for the extraction of unique bioactivecompounds for new products development, and through specimen collection, mitigating negative eﬀects causedby alien species, contributing for ecosystem integrity and sustainability.Over the last decades, the brown seaweed S. muticum and the red A. armata have been studied all over theworld for their capacity to produce bioactive compounds, with main results pointing towards their high potentialas producers of antioxidant, antifouling, antimicrobial, and antitumor compounds.The present review summarizes the biotechnological potential of S. muticum and A. armata as producers ofbioactive compounds, while addressing the potential use of global threats as important blue growth pawns.